Pengaruh Pendapatan Asli Daerah, Dana Bagi Hasil, dan Jumlah Penduduk Terhadap Belanja Daerah di Provinsi Jawa Timur - Laela Nurul Safa'ah; Evi Rahmawati; Arneta Ardelia Novem; Fatkhul Kholifatul Azizah; Saiful Anwar (CV ODIS, 2021)
This study aims to test and analyze the effect of regional original income, profit sharing funds, and population of regional expenditure. This research was conducted in 6 districts/cities in East Java Province. The type of research is to use secondary data originating from the central PPID site in the form of a budget realization report. The data analysis technique used in this study uses a quantitative approach through EVISS 9 software with multiple linear regression analysis methods. The results of this study indicate that the regional revenue variables and the variable number of population has a positive and insignificant effect. Whereas for variables of fund sharing funds have a significant positive effect. From the research that has been done, it is hoped that the local government, especially the Regency/City of East Java Province can explore the potential as a source of Regional Original Revenue and maximize its budget for development and support community welfare.